Development of a Brief Form of the Interpersonal Reactivity Index (B–IRI). Issue 5 (2nd September 2016) - Ingoglia, Sonia; Lo Coco, Alida; Albiero, Paolo
ABSTRACT: The Interpersonal Reactivity Index (IRI) is a standardized self-report measure of disposition to empathic responsiveness for the general adult population (the domain for which it was developed), and for the general adolescent population. The IRI has a number of problems, however, including some uncertainty about its factor structure, low reliabilities, and poor readability of some items for people with limited literacy skills. To address these issues, we constructed an abbreviated form of the index, the Brief IRI (B–IRI). Three studies demonstrated that this 16-item B–IRI has a clear and coherent factor structure, adequate internal consistency, measurement invariance across gender and age, and theoretically meaningful associations with a range of external criteria that support its construct validity. The B–IRI substantially preserves the psychometric properties of the long form, and we recommend its use in all research settings.